Analysing the Factors that Impact Manufacturing Companies’ Financial Performance in Indonesia - Christian Frederick; Merry Susanti (Graduate Program of Universitas Tarumanagara, 2023)
This research was conducted with the aim of obtaining quantitative evidence of the component of intellectual capital, asset management, liquidity, firm size, and leverage on firm’s financial performance. The population used in this research are manufacturing companies listed in Indonesia Stock Exchange for the period of 2017-2020, with a total of 197 companies. The sample in this research was selected using the purposive sampling method with a total sample used of 66 companies. The method of analysis in this research is using the multiple regression analysis which aims to determine the effect of each variable on the companies’ financial performance. The result of this research show that value added capital employed, value added human capital, and asset turnover ratio have a significant effect on financial performance. On the other hand, the structural capital value added, current ratio, size, and debt to asset ratio do not have a significant effect on financial performance.